Tyrosinase Inhibitory of Silver Nanoparticles Synthesized using Morus Nigra Leaves Extract - Tunas Alam; Ricky Ardiansyah; Sharfina Maulidayanti; Deva Azvara; Frida Octavia Purnomo; Dicky Annas (Jurnal Kimia Sains dan Aplikasi, 2023)
A novel preparation of silver nanoparticles using Morus nigra leaves extract, as opposed to the physical and chemical methods had been used in this work. Their active phytochemical compounds will reduce Ag+ and form AgNPs (Ag0). A peak spectrum at 460 nm was formed and confirmed as the Surface Plasmon Resonance (SPR). Vibration at 1643 cm-1 and 3286 cm-1 which characteristic of C=C bonds and (-OH) hydroxyl groups, respectively. An X-ray diffraction (XRD) examination of silver with good crystallinity revealed its distinctive pattern. According to the results of transmission electron microscopy (TEM), the produced AgNPs-Morus nigra leaves extract were between 10 and 20 nm in size. Using L-dihydroxyphenylalanine (L-DOPA) as the substrate, the synthesized AgNPs-Morus nigra were tested for their tyrosinase inhibitory activity, and the results are substantial when compared to kojic acid as a control. The percentages of inhibition from crude extract, AgNPs, and kojic acid at 100 µg/mL are to be found at 12.10 %, 64.80 %, and 59.84 %, respectively. Based on the results of this work, AgNPs can be produced by utilizing a green synthesis method with leaves extract, making them a promising candidate for use in medicine and cosmetics.